2016
DOI: 10.1016/j.heliyon.2016.e00110
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression analysis and recombinant expression of a gene encoding a polygalacturonase-inhibiting protein from tobacco, Nicotiana tabacum

Abstract: Polygalacturonase inhibiting proteins (PGIPs) are major defensive proteins produced by plant cell walls that play a crucial role in pathogen resistance by reducing polygalacturonase (PG) activity. In the present study, a novel PGIP gene was isolated from tobacco (Nicotiana tabacum), hereafter referred as NtPGIP. A full-length NtPGIP cDNA of 1,412 bp with a 186 bp 5′-untranslated region (UTR), and 209 bp 3′-UTR was cloned from tobacco, NtPGIP is predicted to encode a protein of 338 amino acids. The NtPGIP seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…However, studies on heterologous expression of PGIPs, apart from in planta, are scarce and limited to few candidate proteins. Some PGIPs were successfully expressed in Escherichia coli (39,42,44,49), whereas other studies report on their accumulation into inclusion bodies (14,50). When studying novel PGIPs, assessment of whether renaturation restores the native function is difficult, because the target PG is unknown.…”
mentioning
confidence: 99%
“…However, studies on heterologous expression of PGIPs, apart from in planta, are scarce and limited to few candidate proteins. Some PGIPs were successfully expressed in Escherichia coli (39,42,44,49), whereas other studies report on their accumulation into inclusion bodies (14,50). When studying novel PGIPs, assessment of whether renaturation restores the native function is difficult, because the target PG is unknown.…”
mentioning
confidence: 99%
“…The PGIP anti-disease effect has been confirmed in a series of in vivo experiments. PGIP-mediated fungi resistance has been shown in various important cash crops, such as grapes [57,58], papaya [59], potatoes [51], alfalfa [15], cotton [60], green beans [6,28,61], tomatoes [62], peas [63], mandarin orange [64], tobacco [65], and Arabidopsis [66]. PGIP expression does not affect plant phenotype or inhibit plant growth in sugar beet [67] or tobacco [67].…”
Section: Application Of Pgip In Plant Disease Resistance Genetic Engineeringmentioning
confidence: 99%
“…The sialic acids can be utilized by pathogens as nutrients [4] or attachment sites for bacterial adhesion [5]. The study of sialic acid binding adhesins has revealed similar lysine-rich sialic acid binding motifs in lectins on Escherichia coli and Helicobacter pylori [6,7]. A large diversity in mucin glycosylation is observed between species, and also between organs within the same animal [8].…”
Section: Introductionmentioning
confidence: 99%